Principal’s Strategy in Improving Education Quality through School-Based Management - Santana, Dafri; Ahmad, Syarwani; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2024)
The goal of this study is to identify the principal’s approach to improving the quality of education through SD IT Ishlahul Ummah Prabumulih’s school-based management. The method used is a descriptive phenomenological method with data collection methods obtained from the principal, curriculum vice-principal, student school vice-principal, teachers, and supervisors of the school committee. The methods used start from the reduction of data, presentation of data, and conclusions. The results of the study suggest that the strategy of the principal to enhance the quality of education through School-Based Management is included as an implementation program in the medium-term work plan, organizing by creating an Internal Quality Assurance System team to assess programs through school self-evaluation, implementing strategies by completing school facilities Providing incentives for teachers who succeed, enhancing the skills of educators and education workers, improving student success, developing networks with the business world and creating good relationships with the community, and infrastructure to support the quality of education, Though school facilities in the field of sports and prayer rooms are the inhibiting factors for the principal’s strategy, less disciplined students, teachers who are non-linear, as well as the transition from old teachers to new teachers.